Pendidikan Islam, Lembaga Pendidikan, dan Runtuhnya Dinasti Turki Usmani Terhadap Pendidikan - Burhanudin Burhanudin; Ditta Maulida Rahma; Nabila Mufidah Zaen; Gunawan Aji (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
Major changes have brought about the history of the Islamic world, both from political, social and educational aspects. This condition continued until the emergence of three great kingdoms in the middle period of the Islamic world which began to enter its heyday in 1500-1700 AD. The three kingdoms were the Ottoman Empire in Turkey, the Safavid Empire in Persia and the Mughals in India. This research uses a descriptive qualitative method with a historical approach because it discusses past events that occurred during the Ottoman period and literature study by collecting data sources from several books or literature. The results of this research reveal the characteristics of Islamic education during the Ottoman era, starting by describing Islamic education, educational institutions, and the collapse of Ottoman Turkey towards education.